Replacement Effect Of Moina sp With Artificial Feed On Survival And Growth Of Asang Fry (Ostheochilus hasseltii) - Usman Bulanin; Diana Reska Ayu Putri; Amelia Sriwahyuni Lubis; Mas Eriza; Abdullah Munzir (University of Prof. Dr. Hazairin, SH, 2021)
This study aimed to analyze the effect of early replacement of Moina sp with artificial feed on the survival and growth of Asang fish larvae. This research method is an experiment using a completely randomized design (CRD) with 3 treatments and 4 replications. Treatment A was given artificial feed for 30 days, treatment B was given Moina sp for 5 days followed by artificial feed for 25 days and treatment C was given Moina sp for 10 followed by artificial feed for 20 days. The data obtained from the research results were analyzed by statistical test Analysis of variance (ANOVA). To determine the difference between treatments, continued with Duncan’s test. Based on the results of the one-way ANOVA analysis, the initial period of artificial feeding had no significant effect on survival (P>0.05) but had a significant effect on the growth rate of weight and length of Asang fish larvae (P<0.05). Giving Moina sp for 10 days followed by artificial feed gave optimal results followed by giving Moina sp for 5 days followed by artificial feed.